Cover Feature: Multifunctional Shape‐Memory Polymer Foams with Bio‐inspired Antimicrobials (ChemPhysChem 16/2018). Issue 16 (2nd August 2018) - Monroe, Mary Beth Browning; Easley, Alexandra D.; Grant, Katie; Fletcher, Grace K.; Boyer, Calla; Maitland, Duncan J.
Abstract : The Cover Feature illustrates the release of incorporated cinnamic acid from shape memory polymer foams. Cinnamic acid is a honey‐based antimicrobial molecule that acts to kill surrounding bacteria, including E. coli, as depicted here. More information can be found in the Article by M. B. Browning Monroe et al. onpage 1999 in Issue 16, 2018 (DOI:10.1002/cphc.201701015 ).